Rapid Identification of QTL for Mesocotyl Length in Rice Through Combining QTL-seq and Genome-Wide Association Analysis - Wang, Yamei; Liu, Jindong; Meng, Yun; Liu, Hongyan; Liu, Chang; Ye, Guoyou (Frontiers in Genetics, 2021)
Mesocotyl is a crucial organ for pushing buds out of soil, which plays a vital role in seedling emergence and establishment in direct-seeded rice. Thus, identification of quantitative trait loci (QTL) associated with mesocotyl length (ML) could accelerate genetic improvement of rice for direct-seeding cultivation. In this study, QTL-seq applied to 12 F2 populations identified 14 QTL for ML, which were distributed on chromosome 1, 3, 4, 5, 6, 7 and 9 based on Δ(SNP-index) or G-value statistics. Besides, genome-wide association study (GWAS) using two diverse panels identified five unique QTL on chromosomes 1, 8, 9 and 12 (2), respectively, explaining 5.3 to 14.6% of the phenotypic variations. Among these QTL, seven were in the regions harboring known genes or QTLs, whereas the other 10 were potentially novel. Six of the QTL were stable across two or more populations. Eight high confidence candidate genes related to ML were identified for the stable loci based on annotation and expression analysis. Association analysis revealed that two PCR-gel-based markers for the loci co-located by QTL-seq and GWAS, Indel-Chr1:18932318 and Indel-Chr7:15404166 for loci qML1.2 and qML7.2 respectively, were significantly associated with ML in a collection of 140 accessions and could be used as breeder friendly markers in further breeding.